Project WINGS (Women Initiating New Goals of Safety): A randomised controlled trial of a screening, brief intervention and referral to treatment (SBIRT) service to identify and address intimate partner violence victimisation among substance‐using women receiving community supervision. (10th December 2015) - Gilbert, Louisa; Shaw, Stacey A.; Goddard‐Eckrich, Dawn; Chang, Mingway; Rowe, Jessica; McCrimmon, Tara; Almonte, Maria; Goodwin, Sharun; Epperson, Matthew; Gilchrist, Gail; Radcliffe, Polly; McMurran, Mary; et al.
ABSTRACT Background The high rate of intimate partner violence (IPV) victimisation found among substance‐using women receiving community supervision underscores the need for effective IPV victimisation screening, brief intervention and referral to treatment services (SBIRT) for this population. Aims This randomised controlled trial (RCT) aims to assess the feasibility, safety and efficacy of a single‐session computerised self‐paced IPV SBIRT (Computerised WINGS) in identifying IPV victimisation among women under community supervision and increasing access to IPV services, compared to the same IPV SBIRT service delivered by a case manager (Case Manager WINGS). Methods This RCT was conducted with 191 substance‐using women in probation and community court sites in New York City. Results No significant differences were found between Computerised and Case Manager WINGS arms on any outcomes. Both arms reported identical high rates of any physical, sexual or psychological IPV victimisation in the past year (77% for both arms) during the intervention. Both arms experienced significant increases from baseline to the 3‐month follow‐up in receipt of IPV services, social support, IPV self‐efficacy and abstinence from drug use. Conclusions Findings suggest that both modalities of WINGS show promise in identifying and addressing IPV victimisation among substance‐using women receiving community supervision.Copyright © 2015 John Wiley & Sons, Ltd. Copyright © 2015 John Wiley & Sons, Ltd.